2004
DOI: 10.1001/archotol.130.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Presentation-to-Diagnosis Interval in Patients With Oropharyngeal Carcinoma

Abstract: To evaluate the prognostic impact of presentation-to-diagnosis interval (PDI) and its association with other clinical factors in patients with oropharyngeal squamous cell carcinoma (OpSCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 23 publications
2
39
0
5
Order By: Relevance
“…Symptomatically, otalgia has not been previously reported as a presenting feature of laryngeal carcinoma in an HIV/AIDS patient. Otalgia as a symptom in patients with squamous carcinomas of the head and neck is not uncommon (6%-20%) [13,14] and is usually associated with more aggressive disease [13,14]. This symptom occurred in our first patient who, although she was initially staged clinically with a T2N0M0 SCC of the supraglottis, progressed on to having a rapidly metastasizing tumor.…”
Section: Discussionmentioning
confidence: 70%
“…Symptomatically, otalgia has not been previously reported as a presenting feature of laryngeal carcinoma in an HIV/AIDS patient. Otalgia as a symptom in patients with squamous carcinomas of the head and neck is not uncommon (6%-20%) [13,14] and is usually associated with more aggressive disease [13,14]. This symptom occurred in our first patient who, although she was initially staged clinically with a T2N0M0 SCC of the supraglottis, progressed on to having a rapidly metastasizing tumor.…”
Section: Discussionmentioning
confidence: 70%
“…Where delay was considered as a categorical variable, the cutoff time period for delay varied substantially, although several studies considered patient delays of >3 months as being relevant to stage at diagnosis. 9,12,15,16,18,20,23,28,30,33 The biologic basis for a 3-month period of delay was not discussed in any study, although there is indication that this period of delay may be relevant to stage at diagnosis for breast cancer. 36 Because of the great variability in case mix, definitions of delay, and statistical methodologies, we deemed that this literature could not be quantitatively synthesized.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Koinuven et al 29 found no relationship between either patient or provider delays >2 months and stage at diagnosis in multivariate analysis of pharyngeal cancers at all sites. Ho et al 30 found that subjects with provider delays >3 months had a significantly greater likelihood of being diagnosed with tumor, node, metastases (TNM) stage IV oropharyngeal cancer.…”
Section: Diagnostic Delay and Stage At Diagnosis For Pharyngeal Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate analysis in the study of Denis et al [24] also showed stage IV disease as an important factor for short survival. The results of multivariate analysis in the study of Ho et al [59] have also presented overall clinical stage as one of the strongest factors for survival.…”
Section: Discussionmentioning
confidence: 99%